Post-treatment controllers after treatment interruption in chronically HIV-infected patients. (13th March 2018) - Maggiolo, Franco; Di Filippo, Elisa; Comi, Laura; Callegaro, Annapaola
Abstract : Objective: Control HIV replication requires continuous combined antiretroviral therapy (cART) as discontinuation of cART results in a rapid viral rebound. However, a few individuals exist who took cART for several years and did not show the expected viral rebound after treatment cessation. Most post-treatment controllers (PTCs) are early treated individuals. We report three cases who started cART during chronic infection. Design: Patients were treated and monitored according to Italian guidelines. For the description of cases, the percentage of CD8 + CD38 − HLA*DR + cells, CD8 + CD38 – HLA*DR + cells, major histocompatibility complex genotyping, total HIV-DNA and plasma levels of anti-retroviral (ARV) drugs were performed. Results: Patients started therapy during chronic infection. Patient 26636 started her first ARV drug two years after diagnosis and patients 93016 and 50293 started cART with high viral loads and low CD4 + cell counts. Time without cART was 13, 11 and 1.5 years, respectively. None presented any of the protective class I HLA alleles and patient 93016 has the HLA−B*35 allele that appears to be enriched in PTCs. Patients 93016 and 50293 had very low levels of CD8 + CD38 − HLA*DR + cells (<5%) much lower than those of patient 26636 (27%). T-cell-associated HIV-DNA was 3.78, 3.48 and 3.13 log copies/10 6 CD4 +, respectively. Conclusion: Patients like ours may advance our understanding of the characteristics for which individuals may be more likely to achieve ART-free remissions. Furthermore, our patients are among the few so far described who started cART during chronic infection extending the hope that a functional cure is possible even in this setting.